Manajemen Bandwidth Menggunakan Metode PCC pada Jaringan LAN Fakultas Bisnis dan Teknologi Universitas Teknologi Yogyakarta - Aulia Desy Nur Utomo; Ahmad Ashari (LPPM STMIK Widya Utama, 2018)
On the use of the Internet network of a generalnature need to apply the appropriate configuration ofbandwidth management in order to maximize the use ofbandwidth provided by the provider. This is important foroptimal bandwidth usage and according to the utility thatbasically is general and is used together can be achieved. PerConnection Classifier (PCC) is a method of load balancing todistribute the traffic load on more than one networkconnection point in a balanced way, so that traffic can runoptimally. The research focused on the application bandwidthmanagement and network configuration method to maximizethe use of the internet university of each user. Quality ofService is used to look at the performance of the networktraffic that is indicated by the value of the parameter delay,throughput and packet loss. Based on the results of testsperformed, the measurement results are shown basedbandwidth QoS parameters after using PCC and bandwidthmanagement configuration is applied include filtering traffic,limit bandwidth and burst. Results obtained for the delayvalue decreased from 180.26 ms becomes 112.21 ms andthroughput increased from 1.76% to 2.66%, then to packetloss decreased from 25.37% to 15.74% s in accordance withthe standards TIPHON.